The Cambridge sheep — its exploitation for increased efficiency of lamb production - Owen, J. B.; Dewi, I. AP (Agricultural and Food Science, 1988)
The Cambridge breed has been developed since 1964, based on a foundation group of 54 ewes representing 11 breeds mated initially to seven Finnsheep rams. Data presented show that a high litter size(LS) has been established (mean 2.8 in 3 year old ewes) by a policy of selection coupled with minimising generation interval. Observations on ovulation rate (OR)show a large range (1—13) and are consistent with an hypothesis that OR is influenced by a major gene effect superimposed on a basal level of about 2.5 ova. The gene appears to increase ovulation by about two ova per copy and to have a frequency approaching 0.3 in the Bangor University flock. Data on the relationship of LS at birth and of lambs weaned per ewe are presented which indicate that under ideal conditions the optima for OR and LS at birth cannot exceed 5 and 3.5 respectively for mature ewes. The practical utilisation of the breed as a dam-line sire of crossbred ewes show that the Cambridge crossbreds are more precocious, more prolific, have slower growing lambs with carcasses of similar quality to the corresponding Border Leicester crosses. Overall superiority inefficiency of feed utilisation is about 20 %. Methods of genotyping sheep and utilising the major gene in practice are discussed.